Phase equilibria of advanced technology uranium silicide-based nuclear fuel - Ulrich, Tashiema L.; Besmann, Theodore M. (Frontiers in Nuclear Engineering, 2024)
The phases in uranium-silicide binary system were evaluated in regards to their stabilities, phase boundaries, crystal structures, and phase transitions. The results from this study were used in combination with a well assessed literature to optimize the U-Si phase diagram using the CALPHAD method. A thermodynamic database was developed, which could be used to guide nuclear fuel fabrication, could be incorporated into other nuclear fuel thermodynamic databases, or could be used to generate data required by fuel performance codes to model fuel behavior in normal or off-normal reactor operations. The U3Si2 and U3Si5 phases were modeled using the Compound Energy Formalism model with 3 sublattices to account for the variation in composition. The crystal structure used for the USi phase was the tetragonal with an I4/mmm space. Above 450 °C, the U3Si5 phase was modeled. The composition of the USi2 phase was adjusted to USi1.84. The calculated invariant reactions and the enthalpy of formation for the stoichiometric phases were in agreement with experimental data.